Dynamic Eccentric Exercise lmprove GLU-1 Expression on Calf Muscle of Diabetic Mice Models - Purwanto, Bambang (Udayana University Press, 2014)
Previous study we found that Glut-1 was also expressed on calf muscle of diabetic mice models. Exercise was known as one of diabetic modalities therapy but it was still unclear whether exercise improved Glut-1 expression on diabetic muscle. Multiple low dose of streptozotocin administration was used to induce diabetes at mice. Diabetic mice were run on treadmill with negative inclination (downhill) for 21 minutes as dynamic model of eccentric exercise for calf muscle. A significant improvement of Glut-1 expression found optimal at -5 degree of declined treadmill.